Self-Employment Differentials among Foreign-Born STEM and Non-STEM Workers - Zhengyu Cai; John V. Winters (Institute of Labor Economics (IZA), 2017)
This paper uses the American Community Survey to examine the previously overlooked fact that foreign STEM (science, technology, engineering, and mathematics) graduates have much lower self-employment rates than their non-STEM counterparts, with an unconditional difference of 3.3 percentage points. We find empirical support for differing earnings opportunities as a partial explanation for this self-employment gap. High wages in STEM paid-employment combined with reduced earnings in self-employment make self-employment less desirable for STEM graduates. High self-employment rates among other foreign-born workers partially reflect weak paid-employment opportunities. Public policy should encourage efficient use of worker skills rather than low-value business venture creation.
Keywords: F22; J15; J31; L26; 330; self-employment; immigration; foreign-born; college major; STEM; earnings